Human Computer Interaction: Concepts, Methodologies, Tools, and Applications - Zaphiris, Panayiotis; Ang, Chee Siang (My University, 2008)
Containing more than 200 authoritative works from over 250 experts in the field, this groundbreaking collection contains significant chapters on topics such as Web logs, technology influences, and human factors of information systems and technology.